The First Awake Craniotomy for Seizure Focus Resection in Iran 2016 - Mohammadali Attari (Advanced Biomedical Research, 2018)
Patient with refractory seizure may undergo awake craniotomy when the area to be resected is immediately adjacent to eloquent cortex. An awake craniotomy in a 30-year-old man was conducted using a scalp block, dexmedetomidine, and remifentanil infusion without any airway device throughout the procedure. Dexmedetomidine administered at a loading dose of 1 μg/kg and maintenance dose of 0.2–0.7 μg/kg/h. Remifentanil dose was 0.02 μg/kg/min. The patient remained comfortable and hemodynamically stable throughout the procedure. Cortical electrical stimulation revealed motor cortex overlapped with seizure focus. So that surgical procedure was limited to subpial resection of the epileptic focus. Dexmedetomidine with concurrent scalp block appears to be an useful sedation for awake craniotomy when sophisticated neurological test is required.